2021
DOI: 10.1051/e3sconf/202125303083
|View full text |Cite
|
Sign up to set email alerts
|

Application of Music Therapy in Intervention Research of Autistic Children

Abstract: With the continuous development of China's information technology, medical information is also constantly innovating, which is conducive to the diversity and effectiveness of the treatment of various diseases, including autism. Music therapy is the embodiment of the innovation of information media in medical informationization. Music therapy is a kind of information communication medium that uses music to stimulate and hypnotize people and stimulate physical reactions in various forms of music activities to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…When there is an unfulfilled or inappropriate desire, the expectations of the student or child with autism will make them feel ignored, and then there are negative emotions that lead to tantrums. Wang et al (2021), in their study, also showed that music therapy has a positive effect and can reduce depression and stress in children with autism. One of the methods in the music therapy interventions used also reduced the negative emotions experienced (Wang et al, 2021).…”
Section: Special Education [Se] E-issn: 2821-3017mentioning
confidence: 92%
See 2 more Smart Citations
“…When there is an unfulfilled or inappropriate desire, the expectations of the student or child with autism will make them feel ignored, and then there are negative emotions that lead to tantrums. Wang et al (2021), in their study, also showed that music therapy has a positive effect and can reduce depression and stress in children with autism. One of the methods in the music therapy interventions used also reduced the negative emotions experienced (Wang et al, 2021).…”
Section: Special Education [Se] E-issn: 2821-3017mentioning
confidence: 92%
“…Wang et al (2021), in their study, also showed that music therapy has a positive effect and can reduce depression and stress in children with autism. One of the methods in the music therapy interventions used also reduced the negative emotions experienced (Wang et al, 2021). In addition, tantrums are also one of the ways in which they release emotions of dissatisfaction and exude displeasure towards a thing or environment.…”
Section: Special Education [Se] E-issn: 2821-3017mentioning
confidence: 92%
See 1 more Smart Citation
“…There is a large amount of research studying the help and influence of music therapy on autistic children, and the author considers it necessary to further develop this special method of therapy for Autism which starts in infancy and is characterized by language development disorders, social interaction disorders, and repetitive behaviors [1,2]. Music therapy is a kind of psychotherapy.…”
Section: Introductionmentioning
confidence: 99%